Moderately Escalated Hypofractionated (Chemo) Radiotherapy Delivered with Helical Intensity-Modulated Technique in Stage III Unresectable Non-Small Cell Lung Cancer - Donato, Vittorio; Arcangeli, Stefano; Monaco, Alessia; Caruso, Cristina; Cianciulli, Michele; Boboc, Genoveva; Chiostrini, Cinzia; Rauco, Roberta; Pressello, Maria Cristina (Frontiers in Oncology, 2013)
Purpose To assess clinical outcomes and toxicities in patients with stage III unresectable non-small cell lung cancer (NSCLC) treated with a moderately escalated hypofractionated radiotherapy delivered with Helical Intensity-Modulated Technique in combination with sequential or concurrent chemotherapy. Methods and Materials Sixty-one consecutive patients considered non-progressive after 2 cycles of induction chemotherapy were treated with a moderately escalated hypofractionated radiation course of 30 daily fractions of 2.25-2.28 Gy each administered in 6 weeks up to a total dose of 67.5 Gy–68.4 Gy (range, 64.5 Gy–71.3 Gy). Thirty-two received sequential RT after 2 more cycles (total= 4 cycles) of chemotherapy, while twenty-nine were treated with concurrent chemo-radiation. The target was considered the gross tumour volume and the clinically proven nodal regions, without elective nodal irradiation. Results With a median follow up of 27 months (range 6 to 40), one-year and 2-year OS rate for all patients was 77% and 53% respectively, with a median survival duration of 18.6 months in the sequential group and 24.1 months in the concomitant group. No Grade ≥ 4 acute and late toxicity was reported. Acute Grade 3 treatment-related pneumonitis was detected in 10% of patients. Two patients, both receiving the concurrent schedule, developed a Grade 3 acute esophagitis. The overall incidence of late Grade 3 lung toxicity was 5%. No patients experienced a Grade 3 late esophageal toxicity. Conclusions A moderately hypofractionated radiation course delivered with a Helical Intensity-Modulated Technique is a feasible treatment option for patients with unresectable locally advanced NSCLC receiving chemotherapy (sequentially or concurrently). Hypofractionated radiotherapy with a dedicated technique allows safely dose escalation, minimizing the effect of tumor repopulation that may occur with prolonged treatment time.